In silico 3-D structure prediction and molecular docking studies of inosine monophosphate dehydrogenase from Plasmodium falciparum. (December 2017) - Raza, Muslim; Khan, Zahid; Ahmad, Aftab; Raza, Saleem; Khan, Ajab; Mohammadzai, Imdad Ullah; Zada, Shah
Graphical abstract: Highlights: Growing resistance in malarial parasites, particularly in Plasmodium falciparum needs for development of novel drug targets. Inosine monophosphate dehydrogenase (IMPDH) is an important target for antimalarial drug discovery. A homology model for P. falciparum IMPDH was constructed taking human IMPDH (PDB code1NF7 ) as template. Combinatorial library of ribavirin (RVP) derivatives (1347 molecules) was designed. A total of five ribavirin derivatives were identified having greater binding affinity with Plasmodium falciparum IMPDH. Abstract: Growing resistance in malarial parasites, particularly in Plasmodium falciparum needs a serious search for the discovery of novel drug targets. Inosine monophosphate dehydrogenase (IMPDH) is an important target for antimalarial drug discovery process in P. falciparum for the treatment of malaria. In the absence of x-ray crystal structure of this enzyme, homology modeling proved to be a reasonable alternate to study substrate binding mechanisms of this enzyme. In this study, a 3-D homology model for P. falciparum IMPDH was constructed taking human IMPDH (PDB code1NF7 ) as template. Furthermore, an in-silico combinatorial library of ribavirin (RVP) derivatives (1347 molecules) was designed and virtually screened for ligands having selectively greater binding affinity with Plasmodium falciparum IMPDH relative to human IMPDH II. A total of five Ribavirin derivatives were identified as having greater binding affinity (−126 to −108 Kcal/mol and −9.4 to −8.6 Kcal/mol) with Plasmodium falciparum IMPDH. These five inhibitors should be used as selective and potent for Plasmodium falciparum IMPDH. Such type of study will provide information to synthetic medicinal chemist to enhance the potential of compounds (RVP derivatives) as chemotherapeutic agents to fight against the increasing burden of malarial infections.